Rescaling of Access and Property Relations in a Frontier Landscape: Insights from Jambi, Indonesia. Issue 3 (2nd July 2016) - Hein, Jonas; Adiwibowo, Soeryo; Dittrich, Christoph, Rosyani; Soetarto, Endriatmo; Faust, Heiko
Abstract : The recent expansion of protected areas and oil palm plantations in Jambi (Sumatra), Indonesia, has been notably disruptive. This article investigates the scalar dimensions of land conflicts within a privately managed conservation area. We built on qualitative research focusing on struggles related to the formation of two informal settlements within the conservation area. Results indicate that, especially in the context of rapid rescaling (e.g., decentralization), new power constellations emerge, thereby altering preexisting property relations. We argue that competing scales of meaning and regulation are structuring the ability of actors to access land and, consequently, reflect tensions between structure and agency.